+0

# 5j+6c=32

0
443
2

5j+6c=32

1j+3c=10

Oct 18, 2017

#2
+17776
+1

If you are to solve this problem for j and for c, multiply the second equation by 2 and subtract from the first equation.

5j + 6c  =  32                    --->     5j + 6c   =  32

1j + 3c  =  10     --->   x2   --->     2j + 6c  =  20

Subtract                            --->     3j           =  12

Divide by 3                       --->                  j  =  4

Substitute 4 for j in the second equation:  1j + 3c  =  10     --->     1(4) + 3c  =  10     --->     4 + 3c  =  10

Subtract 4 from both sides                                              3c  =  6

Divide by 3                                                                        c  =  2

A solution of this set of equations is:  c = 2  and  j = 4.

Oct 18, 2017

#1
+102474
0

Oct 18, 2017
#2
+17776
+1

If you are to solve this problem for j and for c, multiply the second equation by 2 and subtract from the first equation.

5j + 6c  =  32                    --->     5j + 6c   =  32

1j + 3c  =  10     --->   x2   --->     2j + 6c  =  20

Subtract                            --->     3j           =  12

Divide by 3                       --->                  j  =  4

Substitute 4 for j in the second equation:  1j + 3c  =  10     --->     1(4) + 3c  =  10     --->     4 + 3c  =  10

Subtract 4 from both sides                                              3c  =  6

Divide by 3                                                                        c  =  2

A solution of this set of equations is:  c = 2  and  j = 4.

geno3141 Oct 18, 2017